Accelerated Mobile Pages from JavaScript as Accelerator Tool for Web Service on E-Commerce in the E-Business - Agus Wibowo; Guruh Aryotejo; Mufadhol Mufadhol (Institute of Advanced Engineering and Science, 2018)
E-commerce is a sub-part of E-business which includes all kinds of functions and business activities by using electronic data that has the main purpose to increase corporate profits. One of the strategies used is to automate the existing tasks in E-commerce by utilizing web service facilities, which will significantly save time. The use of smartphones as a primary means of information and communication forces web service application providers to improve their services and facilities, such as websites that can be opened quickly and lightly on smartphone devices. This paper will discuss the benefits of accelerated mobile pages as a coding accelerator tool in the javaScript programming language using XML, HTML and XHTML programming as well as involving the use of SOAP, WSDL and NuSOAP that will run on both HTTP and HTTPS protocols. Using accelerated mobile pages as a means of accelerator tool on E-commerce in E-business can directly improve web service performance. This is very prominent when the site is accessed through a smartphone that has limited resources, in the form of website access will feel fast, easy and light.